Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/acer.14572
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID‐19 Pandemic a High‐Risk Period for College Student Alcohol Use? A Comparison of Three Spring Semesters

Abstract: Background: There has been widespread concern that the COVID-19 pandemic may be a high-risk time for alcohol use among heavy drinking populations such as college students. Initial efforts to evaluate changes in college drinking have not yet accounted for typical drinking patterns within a semester.Methods: To fill this gap, we evaluated how college student drinking patterns changed with the onset of restrictions related to the COVID-19 pandemic during spring 2020 relative to spring 2018 and 2019. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
44
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 37 publications
11
44
3
3
Order By: Relevance
“…For example, 68.2% of Belgian students stated that they had consumed less alcohol during the first lockdown, compared to previous levels [16]. Similarly, a longitudinal study [17] conducted in the United States over three springs (2018, 2019, and 2020) showed that college students did not increase their drinking frequency in 2020 as was typical at the end of the spring semester (in 2018 and 2019). In addition, this study also highlighted that their number of drinks per occasion decreased significantly (28% reduction) during the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, 68.2% of Belgian students stated that they had consumed less alcohol during the first lockdown, compared to previous levels [16]. Similarly, a longitudinal study [17] conducted in the United States over three springs (2018, 2019, and 2020) showed that college students did not increase their drinking frequency in 2020 as was typical at the end of the spring semester (in 2018 and 2019). In addition, this study also highlighted that their number of drinks per occasion decreased significantly (28% reduction) during the onset of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 96%
“…University students have encountered many educational challenges (e.g., widespread transition to remote online learning, changes in assessment and examinations, and disruption to internship placements), which have had a major impact on their habits. During the first lockdown, some studies conducted on the general population [1,12,13] and others studies conducted among students reported a decrease in alcohol consumption, expressed as a reduction in binge drinking [14,15], as well as in the frequency of drinking [16,17]. For example, 68.2% of Belgian students stated that they had consumed less alcohol during the first lockdown, compared to previous levels [16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of alcohol use in United States (U.S.) college students have produced conflicting results with reference to changes related to COVID. On the one hand, two studies suggested increases in alcohol use ( Charles et al, 2021 ; Lechner et al, 2020 ), while three studies found decreases in alcohol use following university closures ( Jaffe et al, 2021 ; Ryerson et al, 2021 ; White et al, 2020 ). A sixth found a complex pattern of changes, with increases in frequency of use that were counteracted by declines in quantity of use and binge drinking, all of which was moderated by pre-COVID use patterns ( Jackson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature has investigated the effects of the pandemic on alcohol use among adolescents, young adults, and college students in the U.S. and found mixed results [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. Decreases in opportunities to socialize related to the pandemic were associated with decreases in alcohol use among college students [ 11 , 12 , 18 , 20 ].…”
mentioning
confidence: 99%
“…Decreases in opportunities to socialize related to the pandemic were associated with decreases in alcohol use among college students [ 11 , 12 , 18 , 20 ]. College students who changed residence to live with parents and those who believed that Covid-19 precaution-taking was important, which presumably was associated with fewer opportunities to socialize, decreased their alcohol use more than their peers [ 11 , 12 , [18] , [19] , [20] ]. Research has also found an important role for stressors in determining alcohol use among U.S. college students during the pandemic [ 24 , 25 ], along with associations between drinking to cope motives and heavier alcohol use [ 17 , 24 ].…”
mentioning
confidence: 99%